2022
DOI: 10.3390/jcm11092388
|View full text |Cite
|
Sign up to set email alerts
|

Are EPA and DHA Derivatives Involved in IBD Remission?

Abstract: Recently, an increase in the incidence of inflammatory bowel disease (IBD) has been observed among children and adolescents. Although the pathogenesis of IBD is not fully elucidated currently, actual research focuses on the occurrence of imbalance between pro- and anti-inflammatory molecules and future identification of the role of cytokines in IBD therapy. The purpose of this study was to compare the concentrations of eicosapentaenoic and docosahexaenoic acid derivatives during both phases of Crohn’s disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Both our study groups showed a very low ω3/ω6 ratio, and for polyunsaturated fatty acids (PUFAs) concerns, we observed a significant decrease in DHA intake in the CD group. DHA exerts potent anti-inflammatory effects through inhibition of TNFα receptor and TLR4 inflammatory signaling pathways and also through anti-inflammatory lipid mediators synthesis [ 27 ]; therefore, it is important that these patients increase their daily DHA intake.…”
Section: Discussionmentioning
confidence: 99%
“…Both our study groups showed a very low ω3/ω6 ratio, and for polyunsaturated fatty acids (PUFAs) concerns, we observed a significant decrease in DHA intake in the CD group. DHA exerts potent anti-inflammatory effects through inhibition of TNFα receptor and TLR4 inflammatory signaling pathways and also through anti-inflammatory lipid mediators synthesis [ 27 ]; therefore, it is important that these patients increase their daily DHA intake.…”
Section: Discussionmentioning
confidence: 99%
“…33 Moreover, a study presented that the level of blood DHA is significantly decreased in the active inflammatory UC relative to UC remission. 35 However, mEVs could improve the content of DHA in plasma, which is useful for colitis remission. In addition, mEVs promote the absorption of n-6 PUFAs such as eicosadienoic acid (EDA) in colonic tissues.…”
Section: Lipids and Lipid-like Moleculesmentioning
confidence: 99%
“…115 lipid mediator derived from the omega-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). 116 RvE1 acts as an agonist for chemerin receptor 23 (Chem R23), a G protein coupled receptor found on neutrophils, macrophages, and dendritic cells. This subsequently inhibits immune cell migration.…”
Section: Improvement Of Local or Systemic Inflammatory Statusmentioning
confidence: 99%
“…These responses can be alleviated by increasing IAP expression through the activation of the inflammatory mediator resolvin E1 (RvE1) . RvE1 is a lipid mediator derived from the omega-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) . RvE1 acts as an agonist for chemerin receptor 23 (Chem R23), a G protein coupled receptor found on neutrophils, macrophages, and dendritic cells.…”
Section: Intestinal Barrier Protection By Iapmentioning
confidence: 99%